2+4secx=-6

Simple and best practice solution for 2+4secx=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+4secx=-6 equation:


Simplifying
2 + 4secx = -6

Solving
2 + 4cesx = -6

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 4cesx = -6 + -2

Combine like terms: 2 + -2 = 0
0 + 4cesx = -6 + -2
4cesx = -6 + -2

Combine like terms: -6 + -2 = -8
4cesx = -8

Divide each side by '4esx'.
c = -2e-1s-1x-1

Simplifying
c = -2e-1s-1x-1

See similar equations:

| 9=8-8a | | m+5(5m+2)=140 | | 4x+3x=85.50 | | p+38=3p+20 | | f(n)=4n+13 | | 2*(230-0.5y)=0 | | 3x+10=-5x-19 | | 0.03-0.1y=0.05 | | 6x-18=x+12 | | 2e^6t=4e^5t | | (y+110)+30=180 | | -8(6x-1)+7(7x-3)-9=7-4 | | 2b-68+2b=180 | | 3y-1+y+37=6y+40-4y | | 2y+3x+3=0 | | (y+30)+110=180 | | (1+m)x^2-3mx+(1-m)=0 | | 3y-1+y+37y=6y+40-4y | | 6(4x+9)-23(x+5)=x-63 | | 2x+1=x+63 | | 3x+10=3x-19 | | 5x+4=-8+3x+2x | | 3y-1+y+3y=6y+40-4y | | y=7x+8kx | | 18x+15=4x+29 | | 10-k=12-1 | | 4p=p+14 | | 8-3h=5h+2 | | 17x^2-16x-12=0 | | -2r-6=12-4r | | -4x-12x=80 | | -6+19x=19x-6 |

Equations solver categories